2020
DOI: 10.3389/fevo.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Floral Fragrance Is Compromised by Herbivory

Abstract: Despite the paramount role of floral fragrance in pollinator attraction and reproduction in flowering plants, we know little about its evolution under natural conditions. Here we show that by reducing herbivore load with pesticide application, plants showed evolutionary changes in their floral fragrance within 4 generations when compared to plants with natural levels of herbivory. We interpret this finding in the context of relaxed physiological and ecological trade-offs with fewer herbivores, potentially faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Herbivore attacks to other parts of the plant or drought can change the composition of floral volatiles(Burkle & Runyon, 2016;Ramos & Schiestl, 2020), which provide additional information regarding changes in the physiological status of the emitter plant (Figure 2B,G). Moreover, it remains unclear whether the neighbouring plants prioritise between floral or leaf volatiles, and which are more important for adaption responses.…”
mentioning
confidence: 99%
“…Herbivore attacks to other parts of the plant or drought can change the composition of floral volatiles(Burkle & Runyon, 2016;Ramos & Schiestl, 2020), which provide additional information regarding changes in the physiological status of the emitter plant (Figure 2B,G). Moreover, it remains unclear whether the neighbouring plants prioritise between floral or leaf volatiles, and which are more important for adaption responses.…”
mentioning
confidence: 99%
“…The lack of divergence in qualitative olfactory receptor sensitivity may stem either from selection on broad olfactory sensitivity or from lack of suitable genetic variation. Selection for broad olfactory sensitivity in interactions may result from plant populations producing complex and variable floral volatile bouquets that may potentially evolve rapidly (Gervasi and Schiestl 2017;Ramos and Schiestl 2020). Under these conditions, reliance on one or a few compounds could be selectively disadvantageous.…”
Section: Discussionmentioning
confidence: 99%
“…A fascinating, yet almost unexplored question is whether and how rapidly receptor sensitivity may co-evolve with plant volatile emission (Schiestl and Dötterl 2012). Floral scent in Lithophragma is chemically highly diverse, both among populations and species (Friberg et al 2013(Friberg et al , 2019, indicating rapid evolutionary divergence in this key floral signal (Ramos and Schiestl 2020). Such pattern of high variability has been found in other nursery pollination systems, too (Dötterl et al 2005;Suinyuy et al 2015;Waelti et al 2008), but contrasts to the highly conserved odor bouquets found in yucca flowers (Svensson et al 2005(Svensson et al , 2006(Svensson et al , 2011.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, we found that neither the honeybees nor the bumblebees extended their proboscises toward tomato floral scent innately ( Figure 5 ). In natural ecosystems, both pollinators and non-pollinators impose selection on plant floral traits [ 48 , 49 ]. Plants use olfactory cues to attract bee pollinators.…”
Section: Discussionmentioning
confidence: 99%